PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MODEL SINEKTIK - Supriyadi., Supriyadi (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2014)
Abstract: The purpose of this research is to improve students' ability to write poetry by applying sinektik models in learning. In accordance with the objectives, the study design and procedures using action research. Researcher as the primary instrument dilengkapai with guidance interview, observation, and field notes. Data were analyzed by three steps: (1) reviewing the data, (2) reducing the data , and (3) concluded the data in accordance with the categories and qualifications set . The results of the study are (1) the ability to describe objects direct analogy analogy on stage the first cycle and second cycle of 100 %. Description of the indicator is (1) interesting objects compared, (2) a complete object elements, (3) the right words in detailing the object, and (4) words in accordance with the details of the object Phase personal analogy in Cycle reached 66.67 % and increased to 97.22 % in Cycle II. Indicator of increased personal analogy is (1) a description of the object analogy varied emotions, (2) expression of emotions in accordance with the analogy of the object, (3) the phrase is varied , and (4) the amount equal to the provision of emotional expression. Phase analogy solid conflict in Cycle I reached 97.22 % and increased to 100 % in Cycle II. Indicator of increased conflict solid analogy is (1) the phrase numbered sixteen, (2) the creation of the word in the phrase is quite adequate. and (3) sufficient insight luas.Kemampuan very well qualified to write poetry amounted to 58.33 % in the first cycle and increased to 80.7 % in Cycle II. Indicator of increased poems are (1) the content of the poem according to the theme, (2) diction and style as well as a rich variety of languages, (3) in accordance with the type of poetry rhyme , and (4) structure consistent line and stanza. Abstrak: Tujuan penelitian ini adalah meningkatkan kemampuan menulis puisi siswa dengan menerapkan model sinektik dalam pembelajaran. Sesuai dengan tujuan, penelitian ini menggunakan rancangan dan prosedur penelitian tindakan kelas. Peneliti sebagai instrumen  utama dilengkapai dengan pedoman wawancara, pedoman observasi, dan catatan lapangan. Data dianalisis dengan tiga langkah yaitu (1) menelaah data, (2) mereduksi data, dan (3) menyimpulkan data sesuai dengan kategori dan kualifikasi yang ditetapkan. Hasil penelitian adalah (1) kemampuan mendeskripsikan objek analogi pada tahap analogi langsung Siklus I dan siklus II 100%. Indikator pendeskripsian adalah (1) objek yang dibandingkan menarik, (2) unsur objek lengkap, (3) kata dalam merinci objek tepat, dan (4) kata dalam rincian sesuai dengan objek. Tahap analogi personal pada Siklus mencapai 66,67%  dan meningkat menjadi 97,22% pada Siklus II. Indikator peningkatan analogi personal adalah (1) gambaran emosi terhadap objek analogi bervariasi, (2) ungkapan emosi sesuai dengan objek analogi, (3) kalimat ungkapan bervariasi, dan (4) jumlah ungkapan emosi sama dengan ketentuan. Tahap analogi konflik padat pada Siklus I mencapai  97,22% dan meningkat menjadi 100% pada Siklus II. Indikator peningkatan analogi konflik padat adalah (1) frase berjumlah enam belas, (2) kreasi kata dalam frase cukup memadai. dan (3) wawasan cukup luas.Kemampuan menulis puisi berkualifikasi sangat baik berjumlah 58,33%  pada Siklus I dan mengalami peningkatan menjadi 80,7 % pada Siklus II. Indikator peningkatan puisi adalah (1) isi puisi sesuai dengan tema, (2) diksi dan gaya bahasa beragam serta kaya, (3) rima sesuai dengan jenis puisi, serta  (4) struktur baris dan bait konsisten. Kata  Kunci: Kemampuan mulis puisi, model sinektik